Fixed-time event-triggered control under denial-of-service attacks - Chatterjee K.; Singh V.K.; Prasun P.; Kamal S.; Ghosh S.; Dinh T.N. (My University, 2025)
In this article, fixed-time event-triggered control is designed for a networked system under denial-of-service (DoS) attacks. At first, fixed-time input-to-state stability (ISS) analysis without DoS is analyzed. Then, fixed-time ISS under DoS is examined under the same control law. Sufficient conditions for the frequency of DoS attacks and the time duration of DoS attacks are obtained so that the closed-loop system retains the fixed-time ISS. A numerical example is also given to demonstrate the outcomes of the proposed methodology. © 2022 European Control Association